Return migration and the age profile of retirement among immigrants - Deborah A. Cobb-Clark; Steven Stillma (IZA Journal of Migration, 2013)
We analyze the relationship between the age profile of retirement within an immigrant population and aggregate return migration rates for individuals from different countries of origin. The latter serves as a proxy for the relative net benefits of return migration to that origin country. Our simple theoretical model illustrates that under reasonable conditions the probability of return migration is maximized at retirement. This implies that different immigrant populations will have different retirement profiles, not only because individual retirement behavior differs, but also because the propensity for return migration varies. Consistent with our theoretical model, we estimate a negative relationship between immigrants' retirement status and the aggregate return migration rate of their fellow countrymen. As theory suggests, this link is strongest for immigrants who are near the retirement age.
Keywords: J26; J01; J08; 330; Retirement; Immigrants; Return migration; Emigration; Australia